Аnalysis Direct Result of Reconstructive Interventions on the Mitral Valve - O. Luchynets (Ukrainian Journal of Cardiovascular Surgery, 2016)
The basis of the study were 218 patients with mitral valve insufficiency who were on the examination and surgical treatment to the National Institute of Cardiovascular Surgery. Amosov AMS of Ukraine from 01.01.2010 to 01.01.2015 years. The average age of patients was 52,8±13,0 years. For the group of patients studied hospital mortality was 2.3%.The research was the identification of prognostic risk factors for hospital mortality that will differentiate approach to study indications for surgical treatment.